Procedural Timeout Compliance Is Improved With Real-Time Clinical Decision Support. Issue 3 (September 2018) - Shear, Torin; Deshur, Mark; Avram, Michael J.; Greenberg, Steven B.; Murphy, Glenn S.; Ujiki, Michael; Szokol, Joseph W.; Vender, Jeffery S.; Patel, Aashka; Wijas, Bryan
Abstract : Purpose: The goal of this study was to assess compliance with a presurgical safety checklist before and after the institution of a surgical flight board displaying a surgical safety checklist with embedded real-time clinical decision support (CDS). We hypothesized that the institution of a surgical flight board with embedded real-time data support would improve compliance with the presurgical safety checklist. Methods: In this prospective, observational trial, surgeon-led procedural timeout compliance for 300 procedures was studied. In phase I (PI), procedural timeouts were performed using a simple paper checklist. In phase II (PII), an electronic surgical flight board with an embedded safety checklist was installed in each operating room, but the timeout procedure consisted of the same paper process as in PI. In phase III (PIII), the flight board safety checklist was used. Ten procedures each from 10 surgeons were evaluated in each phase. Compliance was scored on a 12-point scale with each point representing a different item on the checklist. Results: Timeout compliance in PI ranged from 4.5 to 8.6 and 8.75 to 12 in PIII. All 10 surgeons demonstrated statistically improved compliance from PI to PIII. Compliance was significantly improved in 8 of 12 safety check items. Decreased compliance was not seen with any checklist item. Of the items with CDS, compliance with procedure consent and special safety precautions improved from PI to PIII, as did compliance with display of essential imaging, critical events or concerns, and number of procedures (i.e., >1 surgeon performing procedures). Conclusions: Using the electronic medical record with real-time CDS improves compliance with presurgical safety checklists.